Captain Awesome : the show must go on! - Kirby, Stan (Kirby, Stan. Captain Awesome, 2021)
During a school field trip to Sunnyview Playhouse, Captain Awesome and his friends spring into action after seeing a mysterious Man in Black who seems to be stealing jewels.